Recovery of lithium and transition metals from spent LIBs using low concentration ammonia media - Grigoryev, A.; Abdimomyn, S.; Simonov, M.; Malchik, F. (Chemical Bulletin of Kazakh National University, 2026)
The exponential growth in the consumption of lithium-ion batteries (LIBs) necessitates the development of environmentally benign recycling technologies to address the impending surge in end-of-life waste. This study presents a novel, sustainable hydrometallurgical approach for the recovery of critical metals (Li, Ni, Co) from spent NMC/LCO cathode materials utilizing a low-concentration ammonia system. In contrast to conventional methods relying on high ammonia concentrations (4-6 M), this work demonstrates efficient metal leaching using only 0.5 M NH4OH buffered with ammonium sulfate, employing sodium sulfite (Na2SO3) as a reducing agent to facilitate the breakdown of the oxide matrix. Through systematic optimization, the optimal process parameters were established: 0.5 M NH4OH, 0.273 M (NH4)2SO4, and 0.8 M Na2SO3 at pH 10.5 and 80 °C. Under these conditions, the system achieved leaching efficiencies of 99.6% for Ni, 96.4% for Li, and 89.1% for Co. A distinctive feature of the developed process is the selective retention of manganese; unlike acid leaching, this method retains 76% of manganese in the solid residue, significantly simplifying downstream purification and target component separation. The proposed method offers an eight-fold reduction in ammonia consumption compared to conventional ammoniacal schemes, substantially lowering both operational costs and the carbon footprint of the recycling process.